Higlighting the Gender Perspective of Family Planning in Malang City - Arfida Boedirochminarni; Zainal Arifin (Jurnal Perempuan dan Anak, 2020)
The Gender perspective of family planning participants in Malang, especially in the KB village, Bareng, because according to the Women's Empowerment, Child Protection, Population and Family Planning (DP3AP2KB) Office, is located at Jl. Ki Ageng Gribig No.5 Malang Postal Code 65173. Having a vision that is "The realization of community empowerment, population control and the realization of gender equality and protection of women and children". BKBPM also mediates the strategy and policy direction planned by the Malang city government, namely increasing the empowerment of the poor, increasing the empowerment and protection of women and children. As well as improving the quality of family planning and family welfare (DP3AP2KB, 2016). The results of the discussion stated that the number of family planning participants in RW 08 was 329 or 54.92 percent of the number of PUS (couples of childbearing age) of 599. The most enjoyed contraceptive method is an IUD of 98 or 29.78 percent. Whereas for MKJP KB (long-term method of family planning contraception) participants (Long Term Contraception Method) by 13 or 40.42 percent, and the most usage was NON MKJP which was 59.74 percent. Based on the Gender Perspective, only 66 of the 329 KB participants or only 20% of the male participants are involved. This is based on the results of interviews in the family many mothers who do not approve of her husband using the Vasectomy Contraception method, also due to suspicion if the husband uses it will be misused misused on other women (anonymous), other than that the causes of Unmet need factors: Side effects on health, prohibitions from spouse or husband, discomfort, costs to be incurred, do not want to bother, subjective experience does not use contraception does not occur in pregnancy.